The Correlation between Nurses’ Knowledge Regarding Patient Safety and Nurses’ Behaviors in Drug Management - Anita Rachmawati (University of Muhammadiyah Semarang, 2021)
Nurses’ knowledge regarding patient safety affects nurses’ behaviors in managing drugs related to patient safety. A preliminary study at Sultan Agung Islamic Hospital Semarang showed that nurses’ knowledge regarding patient safety was still low, especially about drug management, including storing, ordering/prescribing and recording, administering, and monitoring drugs. This study aimed to determine the correlation between nurses’ knowledge regarding patient safety and nurses’ behaviors in drug management among nurses in the inpatient units of Sultan Agung Islamic Hospital, Semarang. This research was an observational study with a cross-sectional design. The population was 178 nurses in the inpatient units of the specified hospital with a total sample of 123 respondents. The data were collected using a questionnaire and analyzed using Spearman’s rank correlation test. The results showed a correlation between nurses’ knowledge regarding patient safety and nurses’ behaviors in storing drugs (p=0.001 <ά=0.05), ordering and recording drugs (p=0.000 <ά=0.05), administering drugs (p=0.001 <ά=0.05), and monitoring drugs (p=0.003 <ά=0.05). It is expected that nurses evaluate the drug management implementation in the inpatient units so that patient safety is guaranteed as well as plan and manage their behaviors in managing drugs in the hospital to ensure patient safety.